Kecerdasan Emosional Terhadap Kecemasan Menghadapi Masa Pensiun Pegawai - Emi Puspita Dewi; Jawasi Jawasi; Dalinur M. Nur (Bulletin of Counseling and Psychotherapy, 2022)
The purpose of this study was to determine the effect of emotional intelligence on employee anxiety in facing retirement. The research design used simple linear regression analysis with the Independent variable Emotional Intelligence (X) and the dependent variable Anxiety (Y), the data analysis technique used was the basic assumption test (data normality test, linearity test and homogeneity test), hypothesis testing namely regression test linear. T test and R Square test. The results of the research from a simple linear regression test Y = - 2.870 + 0.866 means that employees who have 86.6% emotional intelligence will be able to suppress the anxiety that exists within themselves so that personal implementation that arises is a calm life and is able to adapt to conditions or the environment . Then the results of the t test (partial) there is an influence between emotional intelligence on anxiety facing retirement, namely -2.563 meaning less than 0.05. And the value of R2 (R Square) is 0.974 or 97.4% while the remaining 2.6% is influenced by other factors such as social support, self-concept and so on which were not examined in this study.